Hybrid biofilm-membrane bioreactor (Bf-MBR) for minimization of bulk liquid-phase organic substances and its positive effect on membrane permeability. (December 2015) - Sun, F.Y.; Li, P.; Li, J.; Li, H.J.; Ou, Q.M.; Sun, T.T.; Dong, Z.J.
Graphical abstract: Highlights: Involvement of attached-growth biofilm in Bf-MBR improve membrane permeability when biofilm dominance in bulk. Biofilm growth and co-existence with suspended solid complicate liquid-phase SMP and BPC content and properties. Proper fixed carrier volume in Bf-MBR is essential in fouling mitigation and membrane permeability maintenance. Abstract: Four biofilm membrane bioreactors (Bf-MBRs) with various fixed carrier volumes (C:M) were operated in parallel to investigate the effect of attached-growth mode biomass involvement to the change of liquid-phase organics characteristics and membrane permeability, by comparing with conventional MBR. The experiments displayed that C:M and co-existence of biofilm with suspended solids in Bf-MBRs resulted in slight difference in pollutants removal effectiveness, and in rather distinct biomass properties and bacterial activities. The membrane permeability and specific resistance of bulk suspension of Bf-MBRs related closely with the liquid-phase organic substance, including soluble microbial products (SMP) and biopolymer cluster (BPC). Compared with conventional MBR, Bf-MBR with proper C:M had a low total biomass content and food-chain, where biofilm formation and its dominance affected liquid-phase organics, especially through reducing their content and minimizing strongly and weakly hydrophobic components with small molecular weight, and thus to mitigate membrane fouling significantly.